Injected Urbanism? Exploring India's Urbanizing Periphery. (15th March 2023) - van Duijne, Robbin Jan; Nijman, Jan; Choithani, Chetan
Abstract: Engaging with different literatures in economic geography, postcolonial urbanism, and planetary urbanization, this article seeks to develop a theoretical understanding of remote urban formations taking shape in India's countryside. The analysis draws on extensive primary data collected at two study sites in Bihar and West Bengal, which rendered an uncommonly rich data set for such remote areas. We observe emergent urban formations that result from densification, expansion, and amalgamation of built-up environments and a massive shift of employment out of the agricultural sector. At the same time, alternative local economic opportunities are scarce, giving way to significant increases in circular labor migration. We introduce the concept of injected urbanism to denote a form of urbanization that is exogenously generated through remittances, in the absence of significant local agglomeration processes. The infusion of remittances drives local economic restructuring and the emergence of a consumption economy. Injected urbanism spurs local development, but its dependence on economic activity elsewhere raises important questions about its sustainability.